Sensitivity of ciprofloxacin and ceftriaxone in children with urinary tract infections - Mehar, M. Faisal; Tashfeen, Javairia; Safdar, Rabia Saleem; Khan, Afsheen Asghar; Iqbal, Bushra; Ain, Qurrat Ul (International Journal of Research in Medical Sciences, 2020)
Background: Urinary tract infections (UTIs) are the 2nd commonest bacterial infections, after respiratory tract infections (RTIs), and may go on to progress into chronic kidney disease among paediatric population. The objective of this study was to determine frequency of sensitivity of ciprofloxacin and ceftriaxone in children with urinary tract infections (UTIs). Methods: This descriptive, cross-sectional study was done at the department of pediatric medicine, Nishtar Hospital, Multan, from 10th August 2019 to 9th January 2020. A total of 165 patients presenting with UTI and aged 2 to 12 years of either gender were included. Urine sample was taken in sterilized container and sent immediately for urine culture and sensitivity tests. Results: In a total of 165 cases, mean age was 5.15±2.50 years while most cases, 113 (68.48%) were between 2 to 6 years of age. Out of the 165 patients, 112 (67.87%) were female representing female to male ratio of 2.1:1. Sensitivity of ciprofloxacin in 53 (32.12%) and ceftriaxone in 107 (64.85%) patients was found. Conclusions: This study showed the sensitivity of ciprofloxacin in 32.12% and ceftriaxone in 64.9% children with UTIs.